2022
DOI: 10.1186/s40643-022-00607-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic engineering and raising temperature enhance recombinant protein production with the cdna1 promoter in Trichoderma reesei

Abstract: The fungus Trichoderma reesei is a powerful host for secreted production of proteins. The promoter of cdna1 gene, which encodes a small basic protein of unknown function and high expression, is commonly used for constitutive protein production in T. reesei. Nevertheless, the production level of proteins driven by this promoter still needs to be improved. Here, we identified that the region 600- to 700-bp upstream of the start codon is critical for the efficiency of the cdna1 promoter. Increasing the copy numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…To further investigate whether interference of Trrab7 affects a step downstream of cellulase gene transcription, and to evidence that the reduced cellulase production of P tcu-rab7 KD is not due to the compromised secretory capability, the major endoglucanase, EG1, was expressed from the constitutive promoter cdna1 at the pyr4 locus of the P tcu - rab7 KD strain and QM9414, respectively [ 40 ]. Both extracellular CMCase activity and SDS–PAGE analyses showed that EG1 produced in P tcu - rab7 KD was comparable with that in QM9414 & P cdna - eg1 when cultured on glucose (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate whether interference of Trrab7 affects a step downstream of cellulase gene transcription, and to evidence that the reduced cellulase production of P tcu-rab7 KD is not due to the compromised secretory capability, the major endoglucanase, EG1, was expressed from the constitutive promoter cdna1 at the pyr4 locus of the P tcu - rab7 KD strain and QM9414, respectively [ 40 ]. Both extracellular CMCase activity and SDS–PAGE analyses showed that EG1 produced in P tcu - rab7 KD was comparable with that in QM9414 & P cdna - eg1 when cultured on glucose (Fig.…”
Section: Resultsmentioning
confidence: 99%